Comparative analysis of higher education quality assurance policies in Chile and El Salvador - Rodríguez, Alixon David Reyes; Hernández, Massiel Carolina Venegas; Pittaluga, Susan Paola Robles; Gallardo-Olivera, Moisés David; Villegas, Miguel Alexander Quintanilla (Edelweiss Applied Science and Technology, 2025)
To analyze the quality assurance policies of higher education in Chile and El Salvador, a qualitative approach was used, with a comparative analysis based on a cross-sectional documentary study. The corpus comprised quality assurance policies and specific ordinary laws in both countries, as well as regulations from the National Accreditation Commission in Chile and the Quality Accreditation Commission in Higher Education in El Salvador. Both countries have achieved levels of autonomy and complexity in establishing a quality culture within higher education institutions, with Chile reaching higher levels of qualification. Although both countries, Chile and El Salvador, have implemented quality evaluation systems in higher education, the realities of each country highlight the need to strengthen regulation and the evolution of these processes. The comparative analysis reveals not only similarities and differences in quality assurance policies but also identifies opportunities for improvement based on regulations, implementation of measures, improvement plans, and best practices in quality assurance.